An Epidemiologic Perspective on Scaphoid Fracture Treatment and Frequency of Nonunion Surgery in the USA. Issue 3 (October 2018) - Dy, Christopher J.; Kazmers, Nikolas H.; Baty, Jack; Bommarito, Kerry; Osei, Daniel A.
Background: Scaphoid fractures treated non-operatively and operatively may be complicated by nonunion. Questions/Purposes: We sought to test the primary hypothesis that the incidence density of scaphoid fracture treatment is higher than previously estimated, to determine the frequency and risk factors for nonunion treatment, and to determine whether the frequency of surgical treatment increased over time. Methods: The MarketScan ® database was queried for all records of treatment (casting and surgery) for closed scaphoid fractures over a 6-year period. We examined subsequent claims to determine frequency of additional procedures for nonunion treatment (revision fixation or vascularized grafting occurring 28 days or more after initial treatment). Trend analyses were used to determine whether changes in frequency of surgical treatment or revision procedure occurred. Results: The estimated incidence density of scaphoid fracture is 10.6 per 100, 000 person-years in a commercially insured population of less than 65 years of age. Of 8923 closed scaphoid fractures, 29 and 71% were treated with surgery and casting, respectively. The frequency of surgical treatment rose significantly, from 22.1% in 2006 to 34.1% in 2012. The frequency of nonunion treatment was 10.8% after surgery and 3% after casting; neither changed over time. Younger age, male sex, and surgical treatment are associated with a higher risk of nonunion treatment. Conclusions: Our estimated incidence of scaphoid fracture is higher than previously reported. The increased enthusiasm in the USA to surgically treat scaphoid fractures is reflected by our trend analysis. The frequency of surgical treatment for presumed nonunion after initial surgical management for closed scaphoid fractures exceeded 10%. Given the increased utilization of surgery, surgeons and patients should be aware of the frequency of nonunion treatment to inform treatment decisions.